PEMBERDAYAAN PANTI ASUHAN BERDIKARI AN- NAWAWI BANDAR LAMPUNG DENGAN KEWIRAUSAHAAN DIGITAL BERBASIS EKONOMI KREATIF - Ade Moussadecq; Muhammad Ariza Eka Yusendra; Handoyo Widi Nugroho; Ni Nyoman Widya Ayu Sekarsari; Bustami Achmad Gani (Jurnal Sinergitas PKM & CSR, 2025)
This community service program aims to assist the An-Nawawi Orphanage in developing digital skills and fostering economic independence through technology-based creative entrepreneurship. The program was implemented through a series of training sessions covering graphic design, product photography, videography, as well as business development and digital marketing. Canva software was used as the primary tool for design, photography, and video editing, while the Business Model Canvas (BMC) approach was applied for simple business planning. The progress results show improved competencies among the children in basic design, digital content production, and branding, alongside the active involvement of the orphanage administrators in drafting the BMC as the foundation for their business plan. The conclusion indicates that this program has successfully provided an early impact by enhancing creativity, confidence, and readiness of both the children and the administrators in utilizing digital technology. However, the main limitation is the absence of full implementation of official social media and digital marketing, as the program is still in its early stage. The contribution of this study lies in strengthening digital capacity in social communities—particularly orphanages—which can serve as a model of community engagement in the fields of visual communication design, creative entrepreneurship, and the digital economy.